2021
DOI: 10.21203/rs.3.rs-331727/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of high adherence to vegetables-and-fruits dietary pattern with quality of life among Chinese women with early stage breast cancer

Abstract: Purpose: Dietary intake and patients’ quality of life (QoL) are important supportive care issues in breast cancer survivorship. This study aimed to identify dietary pattern after breast cancer diagnosis. In addition, the association between dietary patterns and QoL were cross-sectionally investigated.Methods: A breast cancer cohort which included 1462 Chinese women were longitudinally interviewed at four time-points, namely baseline, 18-, 36-, and 60-months after diagnosis. At each follow-up, validated food fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Furthermore, Lei et al have reported that dietary patterns involving a higher intake of grains and animal products are associated with poorer functioning in one's roles, while women who consume more fruits and vegetables have better QOL. This finding may be attributed to the ingredients involved in each of these dietary patterns, including refined grains, red and processed meat, and other foods with a high fat content (34). Demark-Wahnefried et al have reported that, among cancer survivors, a low-fat diet that is high in fruits and vegetables is associated with higher levels of physical functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Lei et al have reported that dietary patterns involving a higher intake of grains and animal products are associated with poorer functioning in one's roles, while women who consume more fruits and vegetables have better QOL. This finding may be attributed to the ingredients involved in each of these dietary patterns, including refined grains, red and processed meat, and other foods with a high fat content (34). Demark-Wahnefried et al have reported that, among cancer survivors, a low-fat diet that is high in fruits and vegetables is associated with higher levels of physical functioning.…”
Section: Discussionmentioning
confidence: 99%